Effect of Zaleplon, a Non-benzodiazepine Hypnotic, on Melatonin Secretion in Rabbits - Hideaki Noguchi; Kazuhiro Kitazumi; Megumi Mori; Yoji Shiobara; Toshiharu Shiba (Elsevier, 2003)
ABSTRACT: Melatonin, a major hormone secreted by the pineal gland, is known to play an important role in regulation of the circadian rhythm. (N-[3-(3-cyanopyrazolo[1,5-a]pyrimidin-7-yl)phenyl]-N-ethylacetamide (zaleplon) is a non-benzodiazepine hypnotic that acts via the benzodiazepine site of the GABAA receptor. In the present study, we investigated the effect of zaleplon on melatonin secretion in rabbits using RIA and compared the effect to triazolam and zopiclone. Zaleplon increased a dose-dependent concentration of melatonin in rabbit plasma collected at 30 min after intravenous administration at doses of 1 and 2 mg/kg. The zaleplon-induced increase in plasma melatonin level was not blocked by flumazenil, a benzodiazepine-receptor antagonist. In contrast, triazolam and zopiclone failed to affect the plasma melatonin level. We also investigated the effect of zaleplon on intracellular cAMP in rat pinealocytes. Consequently, zaleplon had no effect on the intracellular cAMP levels in rat pinealocytes. These results of the present studies suggest that zaleplon may promote melatonin secretion and the elevation of plasma levels of melatonin may suggest an influence of zaleplon on chronobiology.